The Interplay Between Risky Sexual Behaviors and Alcohol Dependence: Genome-Wide Association and Neuroimaging Support for LHPP as a Risk Gene - Polimanti, Renato; Wang, Qian; Meda, Shashwath A; Patel, Krishna T; Pearlson, Godfrey D; Zhao, Hongyu; Farrer, Lindsay A; Kranzler, Henry R; Gelernter, Joel (Neuropsychopharmacology (New York, N.Y.), 2017)
To identify genetic mechanisms involved in the interplay of risky sexual behaviors (RSBs) and alcohol dependence (AD), we conducted genome-wide gene-by-AD (GW-GxAD) analyses of RSB in 3924 alcohol-exposed and sexually experienced subjects. RSBs were defined as a score based on lifetime experiences of unprotected sex and multiple sexual partners. Diagnosis of lifetime AD was defined by DSM-IV criteria. To follow-up the genetic findings, functional magnetic resonance imaging analyses were conducted in an independent sample. A trans-population genome-wide significant signal was identified in LHPP (rs34997829; z=-5.573, p=2.51 × 10 ) in the GxAD analysis that also showed associations in the AD-stratified association analysis (AD z=-2.032 and non-AD z=4.903). The clinical relevance of the result was confirmed by the significant interaction between LHPP rs34997829 and AD with respect to self-reported sexually transmitted disease (STD; z=-2.809, p=4.97 × 10 ). The neuroimaging follow-up analysis of LHPP rs34997829 showed reduced power of the left superior frontal gyrus (t=-3.386, p=9.56 × 10 ) and increased power at the right amygdala (t=3.287, p=1.33 × 10 ) in the resting amplitude of low frequency fluctuations analysis; and reduced activation of the anterior cingulate region (t=-2.961, p=3.69 × 10 ) in the monetary incentive delay task. In conclusion, LHPP locus is associated to AD-RSB interaction; and with brain circuitries previously implicated in the inhibition of risky behavior and impulsiveness, emotional regulation, and impulse control/error monitoring. Thus, LHPP is a strong candidate to influence RSB and STD risk in the context of AD.